Preclinical Development of a Novel Epitope-based DNA Vaccine Candidate against SARS-CoV-2 and Evaluation of Immunogenicity in BALB/c Mice - Kanwal, Khalid *; Lim, Hui Xuan *; Ayaz, Anwar *; Tan, Soon Hao; Hwang, Jung Shan *; Ong, Seng Kai *; Poh, Chit Laa * (Springer, 2024)
The protective efficacies of current licensed vaccines against COVID-19 have significantly reduced as a result of SARS-CoV-2 variants of concern (VOCs) which carried multiple mutations in the Spike (S) protein. Considering that these vaccines were developed based on the S protein of the original SARS-CoV-2 Wuhan strain, we designed a recombinant plasmid DNA vaccine based on highly conserved and immunogenic B and T cell epitopes against SARS-CoV-2 Wuhan strain and the Omicron VOC. Literature mining and bioinformatics were used to identify 6 immunogenic peptides from conserved regions of the SARS-CoV-2 S and membrane (M) proteins. Nucleotide sequences encoding these peptides representing highly conserved B and T cell epitopes were cloned into a pVAX1 vector to form the pVAX1/S2-6EHGFP recombinant DNA plasmid vaccine. The DNA vaccine was intranasally or intramuscularly administered to BALB/c mice and evaluations of humoral and cellular immune responses were performed. The intramuscular administration of pVAX1/S2-6EHGFP was associated with a significantly higher percentage of CD8+ T cells expressing IFN-γ when compared with the empty vector and PBS controls. Intramuscular or intranasal administrations of pVAX1/S2-6EHGFP resulted in robust IgG antibody responses. Sera from mice intramuscularly immunized with pVAX1/S2-6EHGFP were found to elicit neutralizing antibodies capable of SARS-CoV-2 Omicron variant with the ACE2 cell surface receptor. This study demonstrated that the DNA vaccine construct encoding highly conserved immunogenic B and T cell epitopes was capable of eliciting potent humoral and cellular immune responses in mice.